Rebuilding Housing Along the Mississippi Coast Ideas for Ensuring an Adequate Supply of Affordable Housing - Bernstein, Mark A. (RAND Corporation, 2006)
In October 2005, RAND researchers went to Mississippi to help the Governor's Commission on Recovery, Rebuilding, and Renewal and the Affordable Housing Subcommittee of the Infrastructure Issues Committee. They identified policy and implementation options that could help local communities address affordable-housing issues. They considered challenges in providing affordable housing and strategies for dealing with those challenges.